2017
DOI: 10.1117/1.jbo.22.1.016006
|View full text |Cite
|
Sign up to set email alerts
|

Mapping optical path length and image enhancement using quantitative orientation-independent differential interference contrast microscopy

Abstract: We describe the principles of using orientation-independent differential interference contrast (OI-DIC) microscopy for mapping optical path length (OPL). Computation of the scalar two-dimensional OPL map is based on an experimentally received map of the OPL gradient vector field. Two methods of contrast enhancement for the OPL image, which reveal hardly visible structures and organelles, are presented. The results obtained can be used for reconstruction of a volume image. We have confirmed that a standard rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
(68 reference statements)
1
30
0
Order By: Relevance
“…, 2011 ). However, OI-DIC provides better image quality and superior resolution (Supplemental Figure S7) because it employs the full numerical apertures of the condenser and the objective lenses, as well as optical subtraction of the images, followed by computation subtraction ( Shribak et al. , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2011 ). However, OI-DIC provides better image quality and superior resolution (Supplemental Figure S7) because it employs the full numerical apertures of the condenser and the objective lenses, as well as optical subtraction of the images, followed by computation subtraction ( Shribak et al. , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…DIC with two orthogonal shear directions has been used to obtain 2D quantitative phase images 21 , 22 , whereas Mehta et al 23 reported a partially coherent model for DIC 2D imaging. Shribak et al 24 used liquid crystal modulators to change the polarization directions and phase shift modulation. This setup allows them to record the 2D phase-gradient information at two orthogonal directions and reconstruct the optical phase front.…”
Section: Introductionmentioning
confidence: 99%
“…The contrast of DIC images depends on the orientation of specimen and the bias between interfering beams (Oldenbourg & Shribak, 2009). To overcome the limitations of DIC technique, a quantitative OI-DIC microscope has been developed (Shribak & Inoué, 2006;Shribak, 2013;Shribak et al, 2017). OI-DIC provides a novel approach to improving the resolution and the contrast of our images.…”
Section: The Oi-dic Microscope As a Tool For Imaging Transparent Livementioning
confidence: 99%
“…The OPD equals to the product of thickness and refractive index difference and represents the cell dry mass (Barer, 1952;Zangle & Teitell, 2014). The obtained OPD images can be enhanced by using deconvolution or the inverse Riesz transform (Larkin & Fletcher, 2014;Shribak et al, 2017).…”
Section: The Oi-dic Microscope As a Tool For Imaging Transparent Livementioning
confidence: 99%
See 1 more Smart Citation